An integrative cross-omics analysis of DNA methylation sites of glucose and insulin homeostasis - Jun Liu (Nature Portfolio, 2019)
Our understanding of the functional link between differential DNA methylation and type 2 diabetes and obesity remains limited. Here the authors present a blood-based EWAS of fasting glucose and insulin among 4808 non-diabetic Europeans and identify nine CpGs not previously implicated in glucose, insulin homeostasis and diabetes.